Mercenaries in the Army of Hellenistic Athens - Vostrikov, Igor V. (Journal of History Culture and Art Research, 2017)
This article interests in history of armed forces of the antiquity states, their structure, deployment order, the organization of command, evolution of arms, policy strokes, action of armies in the military conflicts, and to their use in internal political fight, as well as to involvement of mercenaries. During the Classical Period of Greek history big fame was gained by armed forces of Athens and Sparta. Athens in the 5th century BC was at the peak of power and pursued active foreign policy which was in many respects supported by powerful army and fleet. The reason of traditionally high interest in history of Athens of the Classical Period including the armed forces history of the polis also lies in it. However Athens and their armed forces suffered a serious loss and got beaten in the Peloponnese war and the final decline of political and military power of Athens occurred after defeat in Lamian war therefore military activity of the polis sharply decreases. Therefore the history of Hellenistic period Athens gets much less attention. Proceeding from it, the purpose of article consists in a research of the role of mercenaries in armed forces of Athens in the period of Hellenism. The leading method of this research is the comparative-historical method allowing tracking mercenaries hire by Athens during the specified period on the basis of a complex sources use. The main research results consist in identification of an order and features of the hired contingents use, their places in armed forces of the polis. Materials of article can be useful to the further scientific research regarding the history of Athens and military ancient history as well as to creating educational and handbooks on this perspective.